The Concept and Theory of Money Demand in the Islamic Perspective: Konsep dan Teori Permintaan Uang dalam Perspektif Islam - Dinda Ayu Guspita; Febi Kasnandi; Fery Gusnardi (Yayasan Lembaga Studi Manarul Ilmi, 2024)
This article discusses the concept and theory of currency demand in Islamic economics. Money has an important role in human history and occupies a very strategic position in the economic system. Money is generally considered by society as a reliable medium for transactions, or can be used to pay for goods and services or to pay off debts. In economics it is called a medium of exchange which can be seen in aggregate form. And in Islamic economics it is expressed in the form of money from al-naqdu, which has three main meanings: al-naqdu which means better, holding, and al-naqdu which also means cash. Money is a medium of exchange used by the general public in the production and trade of goods and services. Money can also come from several sources, such as gold, silver, copper, leather, wood, stone, and the like. Money acts as a medium of exchange for trade goods and services, as well as to facilitate barter transactions. two more specific currency functions, namely the original and derivative functions. There are 2 original functions, namely as a trading medium and a basic unit of calculation. It also plays a role as a trading medium or exchange medium that can facilitate